Polylactic acid (PLA)/halloysite nanotube (HNT) composite mats: Influence of HNT content and modification. (September 2015) - Dong, Yu; Marshall, Jordan; Haroosh, Hazim J.; Mohammadzadehmoghadam, Soheila; Liu, Dongyan; Qi, Xiaowen; Lau, Kin-Tak
Abstract: Polylactic acid (PLA)/halloysite nanotube (HNT) composite mats were successfully fabricated via electrospinning. Composite mats reinforced by both unmodified and modified HNTs with a dispersant BYK-9076 were prepared at the HNT contents of 0, 1, 5 and 10 wt%/v. The influence of HNT content and modification was investigated comprehensively, based on several characterisation techniques such as scanning electron microscopy (SEM), X-ray diffraction (XRD) analysis, mechanical testing, differential scanning calorimetry (DSC), thermogravimetric analysis (TGA) and Fourier transform infrared spectroscopy (FTIR). Typical modified Halpin–Tsai model and modified Halpin–Tsai laminate hybrid model in conventional composite theory were used, which were found difficult to predict the entire experimental data of elastic moduli for PLA/HNT composite mats, possibly arising from the nanosized effect of HNTs and some electrospun PLA nanofibres within composite mats.